A primary dorsal osseous Ewing’s sarcoma hidden as acute paraplegia in a 7-year child: A Case report: Dorsa Ewing’s sarcoma as an acute paraplegia - Sameer Yahya, Farah; Al-Shami, Hieder A'ala (Iranian Journal of Child Neurology, 2022)
Ewing’s sarcoma is a highly malignant bone tumor commonly affecting diaphysis of long bones & pelvic bones. It belongs to a spectrum of neoplastic disease known as the Ewing sarcoma family of tumors (EFT) that have the same histologic, immunohistochemical characteristics and chromosomal translocation. It commonly affects children between the ages of 5-15 years. Spinal involvement might be primary or metastatic. Primary spinal involvement is very rare. We report a 7-year female with acute paraplegia caused by dorsal osseous Ewing’s sarcoma that her presentation mimics other causes of acute lower limb weakness in children. Early detection of this rare case and prompt treatment will ensure better outcomes for the patient.